Glutaraldehyde non-conjugated chitosan polymer fluorophores for selective determination of picric acid via fluorescence resonance energy transfer strategy. (June 2019) - He, Hongkun; Qi, Wenjing; Fu, Yuling; Zhao, Maoyu; Qi, Lin; Li, Rong
Abstract: Water-dispersed glutaraldehyde (GA) non-conjugated chitosan polymer fluorophores (GCPF) with quantum yield of 16% is synthesized by stirring chitosan and GA for 6 h at room temperature in the present work. It is a facile and mild method and fluorescent GCPF can be stabled for two months. Owing to the spectral overlap of fluorescent spectrum of GCPF and absorption spectrum of picric acid (PA), a novel sensitive fluorescent method using fluorescent GCPF for PA detection from 10 nM to 50 μM via fluorescence resonance energy transfer (FRET) strategy is established. The distance between donor of GCPF and acceptor of PA (R0 value) is calculated to be 3.5 nm. FRET method using fluorescent GCPF possesses high sensitivity (LOD of 2.8 nM), and selectivity and fast response within 2 min. Moreover, fluorescent GCPF is also utilized in visual analysis of PA using cotton swabs. Fluorescence quenching effect can be observed by eyes irradiated with 365 nm ultraviolet light at cotton swabs and using GCPF solid on quartz glasses, which paves an effect and wide way for the application of fluorescent GCPF in our daily life. Graphical abstract: Water-dispersed glutaraldehyde (GA) non-conjugated chitosan polymer fluorophores (GCPF) with quantum yield of 16% is synthesized via a facile and mild method by stirring chitosan and GA for 6 h at room temperature. Owing to the spectral overlap of fluorescent spectrum of GCPF and absorption spectrum of picric acid (PA), a novel sensitive fluorescent method using the as-prepared GCPF for PA detection from 10 nM to 50 μM via fluorescence resonance energy transfer (FRET) strategy is established. Image 1 Highlights: Water-dispersed glutaraldehyde (GA) non-conjugated chitosan polymer fluorophores (GCPF) with quantum yield of 16% is synthesized at room temperature. Fluorescent method for PA detection from 10 nM to 50 μM via fluorescence resonance energy transfer (FRET) strategy. Visual analysis of PA under the irradiation of 365 nm ultraviolet light at cotton swabs and using GCPF solid on quartz glasses.